Evaluation of the Relationship between Mitral Valve Prolapse (MVP) and Body Mass Index (BMI): A Review Article - Samim, Hossein; Hosseini, Sara; Jalalyazdi, Majid (BALI MEDICAL JOURNAL, 2016)
Background: Mitral valve prolapse (MVP) is a valvular heart disease in which the two valve flaps of the mitral valve do not close equally, and part of the mitral valve slips backward loosely into the left atrium during systole. In general, MVP is associated with low body mass index (BMI), as confirmed by several studies. However, the reason for the higher prevalence of MVP in patients with low BMI remains unknown. Objectives: There is no reliable evidence on the role of genetics or pathophysiological factors in this correlation, and the hypothesis that the size of BMI may lead to MVP or vice versa has not yet been established. Materials and Methods: In this study, all the articles were evaluated in terms of the inclusion criteria. In total, we found 546 articles via PubMed and Google scholar, out of which 30 articles were mainly focusing on MVP, MVR as the major complication of MVP, and BMI, which were included in this systematic review. Results: Among these reviewed studies, patients with MVP had a lower BMI score compared to the subjects without MVP. The low and high BMI score were 28±5 kg/m and 31±6 kg/m, respectively. Conclusions: In the present study, we concluded that low BMI is directly associated with the occurrence of MVP.